Al Content Effects on Mechanical and Tribological Properties of Cr/CrN/CrAlN Multilayer Nanocomposite Coatings. (November 2019) - Zhang, Xue; Chang, Weijie; Zhang, Hao; Zhou, Zichao; Xie, Shengliang; Duo, Shuwang
Abstract: In this study, four Cr/CrN/CrAlN multilayer nanocomposite coatings with various Al content controlled by Al target power were successfully prepared on 316L stainless steels by plasma enhanced magnetron sputtering (PEMS). The surface morphology, chemical composition, phase structure and surface roughness of the coatings were characterized by SEM, EDS, XRD and AFM, respectively. The micro-hardness, Young's modulus and adhesion of the coatings were measured by nano-indentation and nano-scratch, respectively. The friction and wear behavior of the coatings was investigated by a friction and wear tester. The effects of Al content on the microstructure, mechanical properties and wear resistance of the coatings were studied in detail. Results show that Al content in coatings increased with the increase of Al target power. The coatings exhibited the NaCl crystal structure. As the Al content increased, the hardness, Young's modulus, bonding force and wear resistance of the coatings increased first and then decreased. The Cr/CrN/CrAlN coating with Al content of 37.8% has the optimal comprehensive properties.